Conductive rubber foam material and preparation method thereof
By using the synergistic effect of modified carbon fiber and carbon black in rubber foaming materials, the problem of difficult to take into account both the antistatic performance and the foaming structure in the prior art is solved, and the high-performance antistatic and mechanical properties are achieved, which meets the satisfaction of Requirements in special working environments.
Patent Information
- Application Number
- CN202411420585.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
While improving the antistatic properties of existing rubber foaming materials, it is difficult to take into account both the foaming structure and mechanical properties, and the antistatic properties are unstable, affecting the long-term use effect of the material.
By reasonably proportioning natural rubber, butyl rubber and butyl rubber, and combining the synergistic effects of modified carbon fiber and carbon black, a conductive rubber foam material was developed, and a multi-step modification treatment of modified carbon fiber is used to improve conductive performance and antistatic effect while maintaining the mechanical properties and elasticity of the material.
It achieves the realization of the high performance and elasticity of antistatic performance and foaming effect significantly, meets the needs of high-performance antistatic sole materials in special working environments, and has high performance stability.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber foam materials, and in particular to a conductive rubber foam material and a preparation method thereof. Background Art
[0002] The sole material is an important component of footwear products, which directly affects the comfort, durability and overall performance of the shoes. At present, the sole materials on the market are mainly EVA (ethylene-vinyl acetate copolymer) and rubber. These materials have the characteristics of controllable cost and adjustable performance, which basically meet the needs of the public. However, with the development of society and the improvement of people's living standards, the performance requirements for sole materials are also constantly increasing, especially in special working environments, where higher requirements are placed on the antistatic performance of sole materials.
[0003] Natural rubber (NR), a natural polymer compound with cis-1,4-polyisoprene as the main component, has excellent physical and mechanical properties and processability and is widely used in various fields. The main component of natural rubber (91-94%) is rubber hydrocarbon, and the rest is non-rubber substances such as protein, fatty acid, ash and sugar. It has high elasticity, good alkali resistance and swelling, and a wide operating temperature range.
[0004] However, natural rubber itself is an insulating material, and its resistivity is usually around 10 13 Ω·cm or more, it does not have antistatic properties. In some special working environments, such as electronic product manufacturing workshops, flammable and explosive places, precision instrument operation areas, etc., the accumulation and discharge of static electricity may cause equipment damage, fire and explosion, or personal injury and other safety hazards. Therefore, the development of rubber foam materials with good antistatic properties is of great practical significance.
[0005] At present, the common methods to improve the antistatic properties of rubber materials mainly include: adding conductive fillers: such as carbon black, graphite, metal powder, etc., but these fillers may affect the foaming properties and mechanical properties of the material; using antistatic agents: improving its conductivity by adding specific antistatic agents to the rubber, but the effect may not be long-lasting; surface treatment: applying a conductive coating on the rubber surface, but this method may affect other properties of the material and has limited durability.
[0006] Chinese patent document CN110684245A discloses a graphene natural rubber polymer controlled static mixed foaming material and a preparation method thereof. The graphene natural rubber polymer controlled static mixed foaming material is made of the following raw materials in parts by weight: 55-65 parts of natural rubber, 8-12 parts of 1R isoprene rubber, 12-18 parts of butadiene rubber, 14-17 parts of carbon black for batteries, 2.5-3.5 parts of graphene, 1.1-1.3 parts of silicone oil, 1.8-2.2 parts of controlled static oil, 1.6-1.8 parts of zinc oxide, 1.5-1.7 parts of zinc stearate, 1.8-2.1 parts of stearic acid, 0.95-1.15 parts of a cross-linking agent, 2.3-2.8 parts of a flow aid, and 2.4-2.9 parts of a foaming agent.
[0007] However, these methods still have some problems when applied to rubber foam materials: It is difficult to balance the conductivity and foam structure: Adding conductive fillers may affect the foaming properties of the material, resulting in reduced porosity and increased density. Unstable antistatic properties: The effect of some antistatic treatment methods may weaken over time. Deterioration of mechanical properties: Too much conductive filler may reduce the flexibility and ductility of the rubber matrix.
[0008] In view of the above problems, a new type of conductive rubber foam material is developed, which can significantly improve the antistatic performance of natural rubber while maintaining the excellent properties of natural rubber, and does not affect the foaming structure and other important properties, which has important practical significance and market value. The present invention aims to develop a rubber material with good antistatic performance and foaming structure through innovative material design and preparation method, so as to meet the demand for high-performance antistatic sole materials in special working environments. Summary of the invention
[0009] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a conductive rubber foam material and a preparation method thereof, which achieves good conductive properties and antistatic effects by reasonably proportioning natural rubber, butyl rubber and butadiene rubber, combined with the synergistic effect of modified carbon fiber and carbon black; at the same time, the material maintains the excellent mechanical properties and elasticity of rubber, has appropriate porosity and density, meets various requirements of sole materials, and further improves its comfort and lightweight characteristics.
[0010] In order to achieve the above object, the present invention adopts the following technical solution:
[0011] A conductive rubber foam material is prepared from the following components by weight: 50-65 parts of natural rubber, 20-25 parts of butyl rubber, 10-15 parts of butadiene rubber, 4-12 parts of modified carbon fiber, 5-10 parts of carbon black, 1-2 parts of zinc oxide, 1-3 parts of stearic acid, 1-3 parts of zinc stearate, 0.5-1.2 parts of 1,4-di-tert-butylperoxyisopropylbenzene, and 1.5-2.8 parts of azodicarbonamide.
[0012] Preferably, the method for preparing the modified carbon fiber comprises the following steps:
[0013] (1) immersing the carbon fiber in a nitric acid solution, stirring the solution, filtering, washing, and drying the product to obtain a pretreated carbon fiber;
[0014] Carbon fiber pretreatment: The purpose of this step is to increase the activity and hydrophilicity of the carbon fiber surface. Nitric acid, as a strong oxidant, can introduce oxygen-containing functional groups such as carboxyl (-COOH), hydroxyl (-OH) and carbonyl (C=O) on the carbon fiber surface. These functional groups increase the polarity and reactivity of the carbon fiber surface, providing better binding sites for the subsequent in-situ polymerization of polyaniline. At the same time, these functional groups also increase the hydrophilicity of the carbon fiber, which is conducive to the subsequent water phase reaction.
[0015] Preferably, in step (1), the carbon fiber has a diameter of 10-20 μm and a length of 0.5-3 mm.
[0016] Preferably, in step (1), the usage ratio of carbon fiber and nitric acid solution is 10 g: 100-200 mL, and the concentration of nitric acid solution is 30-68 wt %.
[0017] Preferably, in step (1), the stirring treatment condition is 50-80° C. for 30-60 min; and washing with deionized water.
[0018] Specifically, in step (1), the stirring treatment temperature can be 50, 55, 60, 65, 70, 75, or 80° C., and the treatment time can be 30, 35, 40, 45, 50, 55, or 60 min.
[0019] (2) adding aniline and hydrochloric acid into deionized water to prepare a reaction solution, then immersing the pretreated carbon fiber in the reaction solution, slowly dripping an ammonium persulfate solution under stirring, reacting, filtering, washing, and drying the product to obtain a polyaniline-modified carbon fiber;
[0020] In-situ polymerization of polyaniline on the carbon fiber surface: This is an oxidative polymerization process. Under acidic conditions, aniline is first protonated. Ammonium persulfate acts as an oxidant to initiate the oxidative polymerization of aniline. During the polymerization process, aniline monomers are gradually connected to form polyaniline chains. During the growth process, the polymer chain interacts with the functional groups on the carbon fiber surface, thereby achieving in-situ polymerization and coating on the carbon fiber surface. The final polyaniline layer is conductive and forms a stable bond with the carbon fiber surface.
[0021] Preferably, in step (2), the concentration of aniline in the reaction solution is 0.1-0.5 mol / L, the concentration of hydrochloric acid is 1 mol / L; the concentration of ammonium persulfate solution is 0.1-0.5 mol / L; and the volume ratio of the reaction solution to the ammonium persulfate solution is 1:1.
[0022] Preferably, in step (2), an ammonium persulfate solution is added dropwise at 0-5°C; the reaction time is 4-8 hours; and the mixture is washed alternately with deionized water and ethanol for 3-5 times.
[0023] Specifically, in step (2), the ammonium persulfate solution can be added dropwise at 0, 1, 2, 3, 4, or 5° C., and the reaction time can be 4, 5, 6, 7, or 8 hours.
[0024] (3) Add 4-hydroxycinnamic acid to DMF, then add EDC·HCl and NHS, stir to activate, add polyaniline-modified carbon fiber to the activation solution, add triethylamine to adjust the pH, stir to react, filter, wash and dry the product to obtain the modified carbon fiber.
[0025] 4-Hydroxycinnamic acid grafting: This step is to graft 4-hydroxycinnamic acid onto the surface of polyaniline modified carbon fiber through an amidation reaction. First, EDC and NHS activate the carboxyl group of 4-hydroxycinnamic acid to form an active ester intermediate. This intermediate then undergoes a nucleophilic addition reaction with the amino group (-NH2) on the surface of polyaniline to form a stable amide bond. The addition of triethylamine adjusts the pH value to ensure that the reaction is carried out under optimal conditions. It may also promote the deprotonation of the amino group on the surface of polyaniline and enhance its nucleophilicity. This step introduces 4-hydroxycinnamic acid groups with specific functions on the surface of polyaniline modified carbon fiber, further changing the surface properties of the material.
[0026] Preferably, in step (3), the concentration of 4-hydroxycinnamic acid is 0.05-0.2 mol / L, the concentration of EDC·HCl and NHS is 0.05-0.2 mol / L; and the ratio of polyaniline modified carbon fiber to activation solution is 10 g: 200-500 mL.
[0027] Preferably, in step (3), triethylamine is added to adjust the pH to 6-8; the reaction is stirred at 20-30° C. for 12-24 h; and the mixture is washed with DMF, ethanol, and deionized water for 3-5 times in sequence.
[0028] Specifically, in step (3), the pH value can be adjusted to 6, 6.5, 7, 7.5, or 8; the stirring reaction temperature can be 20, 25, or 30° C.; and the stirring reaction time can be 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, or 24 h.
[0029] The present invention also claims a method for preparing the conductive rubber foam material, comprising the following steps:
[0030] The natural rubber is put into an internal mixer, plasticized at 120-125° C. for 10-15 minutes, and stored at room temperature for 48 hours for standby use; the plasticized natural rubber, butyl rubber, butadiene rubber, modified carbon fiber, carbon black, zinc oxide, stearic acid, and zinc stearate are put into an internal mixer for mixing, the material is turned over for the first time at 100-105° C., the material is turned over for the second time at 110-115° C., and the mixing is continued for 7-12 minutes; the material is turned over for the third time at 120-125° C., 1,4-di-tert-butyl peroxyisopropylbenzene is added and mixed for 4-7 minutes, and azodicarbonamide is added and mixed for 7-10 minutes to obtain a mixture, and the conductive rubber foam material is obtained after foaming.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention provides a conductive rubber foam material, wherein natural rubber is used as the main matrix to provide good elasticity and mechanical strength; butyl rubber enhances the aging resistance and air tightness of the material; and cis-1,2-butadiene rubber improves the wear resistance and elasticity of the material. The synergistic effect of modified carbon fiber and carbon black achieves excellent conductive properties and antistatic effects without significantly affecting the foaming structure of the material. Zinc oxide, stearic acid and zinc stearate are used as activators and lubricants to optimize the processing performance and vulcanization characteristics of the material. 1,4-di-tert-butylperoxyisopropylbenzene is used as a cross-linking agent to ensure the formation of the network structure of the material and improve its physical and mechanical properties. Azodicarbonamide is used as a foaming agent to achieve a uniform microporous structure while ensuring conductivity, thereby improving the lightweight characteristics and comfort of the material. The synergistic effect of multiple components enables the conductive rubber foam material of the present invention to achieve excellent conductive properties and foaming effects while maintaining excellent mechanical properties and elasticity, thereby meeting the multi-faceted requirements for high-performance antistatic sole materials under special working environments.
[0033] (2) The present invention provides a method for preparing modified carbon fiber, firstly, nitric acid is used to treat the carbon fiber surface to generate oxygen-containing functional groups such as carboxyl and hydroxyl groups, thereby increasing the surface activity; then, aniline is polymerized under acidic conditions, and the formed polyaniline is mainly combined with the carbon fiber surface through multiple ways such as π-π interaction, hydrogen bonding, electrostatic interaction, and physical entanglement, while introducing a large number of amino and imine groups; finally, the carboxyl group of 4-hydroxycinnamic acid undergoes amidation reaction with the amino group on the surface of polyaniline under the activation of EDC·HCl and NHS to form a covalent bond connection. This step-by-step modification method not only introduces new functional groups at each step, but also ensures the stability of the modification through multiple interactions and chemical bonding, and finally obtains modified carbon fiber with multiple functions.
[0034] (3) The present invention provides a modified carbon fiber, and the multi-step modification process greatly improves the uniformity of the dispersion of the carbon fiber in the foaming material, which is not only conducive to the formation of a stable conductive network, but also ensures that the conductive rubber foaming material maintains stable performance during long-term use. The introduction of polyaniline not only provides additional conductive channels, but also improves the dispersion of the carbon fiber. The grafting of 4-hydroxycinnamic acid further optimizes the surface properties of the carbon fiber and enhances its chemical interaction with the rubber molecules. The introduced cinnamate group has excellent ultraviolet absorption ability and significantly improves the anti-ultraviolet performance of the material. The double bonds in 4-hydroxycinnamic acid can be chemically bonded with the unsaturated components in the rubber matrix, giving the modified carbon fiber excellent low migration, while enhancing the material's antioxidant ability and long-term antistatic properties. The modified carbon fiber can achieve excellent conductive effect at a relatively low addition amount, and will not significantly affect the foaming performance and mechanical properties of the rubber material, which is a key factor in the present invention to achieve high-performance conductive rubber foaming materials. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0036] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.
[0037] Natural rubber was purchased from Hengshui Shuangli Rubber Technology Co., Ltd., model STR5;
[0038] Butyl rubber was purchased from Yanshan Petrochemical, model 1751;
[0039] Butadiene rubber was purchased from Beijing Yanshan Branch of Sinopec, model BR9000;
[0040] Carbon black was purchased from Shanghai Cabot Chemical Co., Ltd., model N234.
[0041] A method for preparing a conductive rubber foam material comprises the following steps:
[0042] (1) 10 g of carbon fiber was immersed in 100-200 mL of 30-68 wt% nitric acid solution, stirred at 50-80 °C for 30-60 min, the product was filtered, washed with deionized water, and dried to obtain pretreated carbon fiber;
[0043] (2) Aniline and hydrochloric acid were added to deionized water to prepare a reaction solution, wherein the concentration of aniline was 0.1-0.5 mol / L and the concentration of hydrochloric acid was 1 mol / L. Subsequently, 10 g of pretreated carbon fiber was immersed in 500 mL of the reaction solution, and 500 mL of 0.1-0.5 mol / L ammonium persulfate solution was slowly added dropwise under stirring at 0-5 °C for 4-8 h. The product was filtered, and washed alternately with deionized water and ethanol for 3-5 times, and dried to obtain polyaniline-modified carbon fiber.
[0044] (3) Add 4-hydroxycinnamic acid to 100 mL of DMF, then add EDC·HCl and NHS, stir and activate, the concentration of 4-hydroxycinnamic acid in the activation solution is 0.05~0.2 mol / L, the concentration of EDC·HCl and NHS is 0.05~0.2 mol / L, add 10 g of polyaniline modified carbon fiber to 200~500 mL of the activation solution, add triethylamine to adjust the pH to 6~8, stir and react at 20~30°C for 12~24 hours, filter the product, wash it with DMF, ethanol and deionized water for 3~5 times in sequence, and dry it to obtain the modified carbon fiber;
[0045] (4) 50-65 g of natural rubber is put into an internal mixer, and plasticized at 120-125° C. for 10-15 min, and stored at room temperature for 48 h for use; the plasticized natural rubber, 20-25 g of butyl rubber, 10-15 g of butadiene rubber, 4-12 g of modified carbon fiber, 5-10 g of carbon black, 1-2 g of zinc oxide, 1-3 g of stearic acid, and 1-3 g of zinc stearate are put into an internal mixer for mixing, and the material is turned over for the first time at 100-105° C., and the material is turned over for the second time at 110-115° C., and the mixing is continued for 7-12 min; the material is turned over for the third time at 120-125° C., 0.5-1.2 g of 1,4-di-tert-butylperoxyisopropylbenzene is added, and the material is mixed for 4-7 min, and 1.5-2.8 g of azodicarbonamide is added, and the mixing is continued for 7-10 min to obtain a mixture, and the conductive rubber foam material is obtained after foaming.
[0046] The present invention will be further described below through specific embodiments.
[0047] Example 1
[0048] A method for preparing a conductive rubber foam material comprises the following steps:
[0049] (1) 10 g of carbon fiber was immersed in 100 mL of 68 wt% nitric acid solution, stirred at 80 °C for 30 min, the product was filtered, washed with deionized water, and dried to obtain pretreated carbon fiber;
[0050] (2) Aniline and hydrochloric acid were added to deionized water to prepare a reaction solution, wherein the concentration of aniline was 0.5 mol / L and the concentration of hydrochloric acid was 1 mol / L. Subsequently, 10 g of pretreated carbon fiber was immersed in 500 mL of the reaction solution, and 500 mL of 0.5 mol / L ammonium persulfate solution was slowly dripped into the solution under stirring at 5 °C for 4 h. The product was filtered, washed alternately with deionized water and ethanol for 3 times, and dried to obtain polyaniline modified carbon fiber.
[0051] (3) 4-hydroxycinnamic acid was added to 100 mL of DMF, followed by the addition of EDC·HCl and NHS, and the mixture was stirred for activation. The concentration of 4-hydroxycinnamic acid in the activation solution was 0.2 mol / L, and the concentrations of EDC·HCl and NHS were 0.2 mol / L. 10 g of polyaniline-modified carbon fiber was added to 500 mL of the activation solution, and triethylamine was added to adjust the pH to 8. The mixture was stirred for reaction at 30°C for 12 h, and the product was filtered, washed three times with DMF, ethanol, and deionized water in sequence, and dried to obtain the modified carbon fiber.
[0052] (4) 6.5 kg of natural rubber was put into an internal mixer, and plasticized at 123° C. for 12 min, and stored at room temperature for 48 h for use; the plasticized natural rubber, 2.5 kg of butyl rubber, 1.5 kg of butadiene rubber, 1.2 kg of modified carbon fiber, 1 kg of carbon black, 0.2 kg of zinc oxide, 0.3 kg of stearic acid, and 0.3 kg of zinc stearate were put into an internal mixer for mixing, and the material was turned over for the first time at 103° C., and the material was turned over for the second time at 112° C., and the mixing was continued for 9 min; the material was turned over for the third time at 122° C., 0.12 kg of 1,4-di-tert-butylperoxyisopropylbenzene was added, and the material was mixed for 5 min, and 0.28 g of azodicarbonamide was added and the material was mixed for 8 min to obtain a mixture, and the conductive rubber foam material was obtained after foaming.
[0053] Example 2
[0054] A method for preparing a conductive rubber foam material comprises the following steps:
[0055] (1) 10 g of carbon fiber was immersed in 100 mL of 54 wt% nitric acid solution, stirred at 70 ° C for 40 min, the product was filtered, washed with deionized water, and dried to obtain pretreated carbon fiber;
[0056] (2) Aniline and hydrochloric acid were added to deionized water to prepare a reaction solution, wherein the concentration of aniline was 0.4 mol / L and the concentration of hydrochloric acid was 1 mol / L. Subsequently, 10 g of pretreated carbon fiber was immersed in 500 mL of the reaction solution, and 500 mL of 0.4 mol / L ammonium persulfate solution was slowly dripped into the solution under stirring at 4 °C. The reaction was continued for 5 h. The product was filtered, and washed alternately with deionized water and ethanol for 3 times, and dried to obtain polyaniline-modified carbon fiber.
[0057] (3) 4-hydroxycinnamic acid was added to 100 mL of DMF, followed by the addition of EDC·HCl and NHS, and the mixture was stirred for activation. The concentration of 4-hydroxycinnamic acid in the activation solution was 0.15 mol / L, and the concentrations of EDC·HCl and NHS were 0.15 mol / L. 10 g of polyaniline-modified carbon fiber was added to 400 mL of the activation solution, and triethylamine was added to adjust the pH to 7. The mixture was stirred for reaction at 26°C for 16 h, and the product was filtered, washed three times with DMF, ethanol, and deionized water in sequence, and dried to obtain the modified carbon fiber.
[0058] (4) 6 kg of natural rubber was put into an internal mixer, and plasticized at 123° C. for 12 min, and stored at room temperature for 48 h for use; the plasticized natural rubber, 2.4 kg of butyl rubber, 1.4 kg of butadiene rubber, 1 kg of modified carbon fiber, 0.8 kg of carbon black, 0.18 kg of zinc oxide, 0.24 kg of stearic acid, and 0.24 kg of zinc stearate were put into an internal mixer for mixing, and the material was turned over for the first time at 103° C., and the material was turned over for the second time at 112° C., and the mixing was continued for 9 min; the material was turned over for the third time at 122° C., 0.1 kg of 1,4-di-tert-butylperoxyisopropylbenzene was added, and the material was mixed for 5 min, and 0.24 kg of azodicarbonamide was added, and the material was mixed for 8 min to obtain a mixture, and the conductive rubber foam material was obtained after foaming.
[0059] Example 3
[0060] A method for preparing a conductive rubber foam material comprises the following steps:
[0061] (1) 10 g of carbon fiber was immersed in 100 mL of 42 wt% nitric acid solution, stirred at 60 ° C for 50 min, the product was filtered, washed with deionized water, and dried to obtain pretreated carbon fiber;
[0062] (2) Aniline and hydrochloric acid were added to deionized water to prepare a reaction solution, wherein the concentration of aniline was 0.2 mol / L and the concentration of hydrochloric acid was 1 mol / L. Subsequently, 10 g of pretreated carbon fiber was immersed in 500 mL of the reaction solution, and 500 mL of 0.2 mol / L ammonium persulfate solution was slowly dripped into the solution under stirring at 2 °C for 6 h. The product was filtered, washed alternately with deionized water and ethanol for 3 times, and dried to obtain polyaniline modified carbon fiber.
[0063] (3) 4-hydroxycinnamic acid was added to 100 mL of DMF, followed by the addition of EDC·HCl and NHS, and the mixture was stirred for activation. The concentration of 4-hydroxycinnamic acid in the activation solution was 0.1 mol / L, and the concentrations of EDC·HCl and NHS were 0.1 mol / L. 10 g of polyaniline-modified carbon fiber was added to 300 mL of the activation solution, and triethylamine was added to adjust the pH to 7. The mixture was stirred for reaction at 22° C. for 20 h, and the product was filtered, washed three times with DMF, ethanol, and deionized water in sequence, and dried to obtain the modified carbon fiber.
[0064] (4) 5.5 kg of natural rubber was put into an internal mixer, and plasticized at 123° C. for 12 min, and stored at room temperature for 48 h for use; the plasticized natural rubber, 2.3 kg of butyl rubber, 1.2 kg of butadiene rubber, 0.7 kg of modified carbon fiber, 0.7 kg of carbon black, 0.14 kg of zinc oxide, 0.16 kg of stearic acid, and 0.16 kg of zinc stearate were put into an internal mixer for mixing, and the material was turned over for the first time at 103° C., and the material was turned over for the second time at 112° C., and the mixing was continued for 9 min; the material was turned over for the third time at 122° C., 0.07 kg of 1,4-di-tert-butylperoxyisopropylbenzene was added, and the material was mixed for 5 min, and 0.22 kg of azodicarbonamide was added and the material was mixed for 8 min to obtain a mixture, and the conductive rubber foam material was obtained after foaming.
[0065] Example 4
[0066] A method for preparing a conductive rubber foam material comprises the following steps:
[0067] (1) 10 g of carbon fiber was immersed in 100 mL of 30 wt% nitric acid solution, stirred at 50 °C for 60 min, the product was filtered, washed with deionized water, and dried to obtain pretreated carbon fiber;
[0068] (2) Aniline and hydrochloric acid were added to deionized water to prepare a reaction solution, wherein the concentration of aniline was 0.1 mol / L and the concentration of hydrochloric acid was 1 mol / L. Subsequently, 10 g of pretreated carbon fiber was immersed in 500 mL of the reaction solution, and 500 mL of 0.1 mol / L ammonium persulfate solution was slowly dripped into the solution under stirring at 0 °C for 8 h. The product was filtered, washed alternately with deionized water and ethanol for 3 times, and dried to obtain polyaniline-modified carbon fiber.
[0069] (3) 4-hydroxycinnamic acid was added to 100 mL of DMF, followed by the addition of EDC·HCl and NHS, and the mixture was stirred for activation. The concentration of 4-hydroxycinnamic acid in the activation solution was 0.05 mol / L, and the concentrations of EDC·HCl and NHS were 0.05 mol / L. 10 g of polyaniline-modified carbon fiber was added to 200 mL of the activation solution, and triethylamine was added to adjust the pH to 6. The mixture was stirred for reaction at 20° C. for 24 h, and the product was filtered, washed three times with DMF, ethanol, and deionized water in sequence, and dried to obtain the modified carbon fiber.
[0070] (4) 5 kg of natural rubber was put into an internal mixer, and plasticized at 123° C. for 12 min, and stored at room temperature for 48 h for use; the plasticized natural rubber, 2 kg of butyl rubber, 1 kg of butadiene rubber, 0.4 kg of modified carbon fiber, 0.5 kg of carbon black, 0.1 kg of zinc oxide, 0.1 kg of stearic acid, and 0.1 kg of zinc stearate were put into an internal mixer for mixing, and the material was turned over for the first time at 103° C., and the material was turned over for the second time at 112° C., and the mixing was continued for 9 min; the material was turned over for the third time at 122° C., 0.05 kg of 1,4-di-tert-butylperoxyisopropylbenzene was added, and the material was mixed for 5 min, and 0.15 kg of azodicarbonamide was added, and the material was mixed for 8 min to obtain a mixture, and the conductive rubber foam material was obtained after foaming.
[0071] Comparative Example 1
[0072] A method for preparing a rubber foam material comprises the following steps:
[0073] (1) 10 g of carbon fiber was immersed in 100 mL of 68 wt% nitric acid solution, stirred at 80 °C for 30 min, the product was filtered, washed with deionized water, and dried to obtain pretreated carbon fiber;
[0074] (2) Aniline and hydrochloric acid were added to deionized water to prepare a reaction solution, wherein the concentration of aniline was 0.5 mol / L and the concentration of hydrochloric acid was 1 mol / L. Subsequently, 10 g of pretreated carbon fiber was immersed in 500 mL of the reaction solution, and 500 mL of 0.5 mol / L ammonium persulfate solution was slowly dripped into the solution under stirring at 5 °C for 4 h. The product was filtered, washed alternately with deionized water and ethanol for 3 times, and dried to obtain polyaniline modified carbon fiber.
[0075] (3) 6.5 kg of natural rubber was put into an internal mixer, and plasticized at 123° C. for 12 min, and stored at room temperature for 48 h for use; the plasticized natural rubber, 2.5 kg of butyl rubber, 1.5 kg of butadiene rubber, 1.2 kg of polyaniline modified carbon fiber, 1 kg of carbon black, 0.2 kg of zinc oxide, 0.3 kg of stearic acid, and 0.3 kg of zinc stearate were put into an internal mixer for mixing, and the material was turned over for the first time at 103° C., and the material was turned over for the second time at 112° C., and the mixing was continued for 9 min; the material was turned over for the third time at 122° C., 0.12 kg of 1,4-di-tert-butylperoxyisopropylbenzene was added, and the material was mixed for 5 min, and 0.28 kg of azodicarbonamide was added, and the material was mixed for 8 min to obtain a mixture, and the rubber foam material was obtained after foaming.
[0076] Comparative Example 2
[0077] A method for preparing a rubber foam material comprises the following steps:
[0078] (1) 10 g of carbon fiber was immersed in 100 mL of 68 wt% nitric acid solution, stirred at 80 °C for 30 min, the product was filtered, washed with deionized water, and dried to obtain pretreated carbon fiber;
[0079] (2) 6.5 kg of natural rubber was put into an internal mixer, and plasticized at 123° C. for 12 min, and stored at room temperature for 48 h for use; the plasticized natural rubber, 2.5 kg of butyl rubber, 1.5 kg of butadiene rubber, 1.2 kg of pretreated carbon fiber, 1 kg of carbon black, 0.2 kg of zinc oxide, 0.3 kg of stearic acid, and 0.3 kg of zinc stearate were put into an internal mixer for mixing, and the material was turned over for the first time at 103° C., and the material was turned over for the second time at 112° C., and the mixing was continued for 9 min; the material was turned over for the third time at 122° C., 0.12 kg of 1,4-di-tert-butylperoxyisopropylbenzene was added, and the material was mixed for 5 min, and 0.28 kg of azodicarbonamide was added, and the material was mixed for 8 min to obtain a mixture, and the rubber foam material was obtained after foaming.
[0080] The performance tests of the rubber foam materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were carried out, and the hardness was tested with reference to GB / T531.1-2008 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore hardness method (Shore hardness)"; the resilience was tested with reference to GB / T 1681-2009 "Determination of resilience of vulcanized rubber"; the tensile strength and elongation at break were tested with reference to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; the tear strength was tested with reference to GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)"; and the ultraviolet lamp with a wavelength of 280~315nm and a temperature of 50W / m was used with reference to GB / T 14522-2008 "Artificial weathering test method for plastics, coatings and rubber materials for mechanical industrial products - fluorescent ultraviolet lamp" 2 After 500 hours of irradiation, the tensile strength retention rate and elongation at break retention rate of the sample were calculated; the surface resistance was tested with reference to GB / T 31838.2-2019 "Dielectric and resistive properties of solid insulating materials Part 2: Resistance properties (DC method) Volume resistance and volume resistivity"; specific data are shown in Table 1.
[0081] Table 1 Test results of rubber foam material properties
[0082] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Shore Hardness 63 62 60 58 54 53 Resilience(%) 59 58 56 56 54 51 Tensile strength(MPa) 6.7 6.5 6.3 6.1 5.8 5.3 Elongation at break (%) 521 514 510 503 486 437 Trouser tearing (N / mm) 9.3 9.1 8.7 8.6 8.2 7.5 Tensile strength retention rate (%) 91.3 90.9 90.6 89.7 78.5 76.3 Retention rate of elongation at break (%) 90.7 90.3 89.5 89.1 73.4 70.2 Surface resistance(Ω) <![CDATA[5.3×10 4 ]]> <![CDATA[6.1×10 4 ]]> <![CDATA[7.2×10 4 ]]> <![CDATA[7.7×10 4 ]]> <![CDATA[7.6×10 4 ]]> <![CDATA[1.3×10 6 ]]>
[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A conductive rubber foam material, characterized in that: The invention is prepared from the following components by weight: 50-65 parts of natural rubber, 20-25 parts of butyl rubber, 10-15 parts of butadiene rubber, 4-12 parts of modified carbon fiber, 5-10 parts of carbon black, 1-2 parts of zinc oxide, 1-3 parts of stearic acid, 1-3 parts of zinc stearate, 0.5-1.2 parts of 1,4-di-tert-butylperoxyisopropylbenzene, and 1.5-2.8 parts of azodicarbonamide; The method for preparing the modified carbon fiber comprises the following steps: (1) immersing the carbon fiber in a nitric acid solution, stirring the solution, filtering, washing, and drying the product to obtain a pretreated carbon fiber; (2) adding aniline and hydrochloric acid into deionized water to prepare a reaction solution, then immersing the pretreated carbon fiber in the reaction solution, slowly dripping an ammonium persulfate solution under stirring, reacting, filtering, washing, and drying the product to obtain a polyaniline-modified carbon fiber; (3) Add 4-hydroxycinnamic acid to DMF, then add EDC·HCl and NHS, stir to activate, add polyaniline-modified carbon fiber to the activation solution, add triethylamine to adjust the pH, stir to react, filter, wash and dry the product to obtain the modified carbon fiber.
2. The conductive rubber foam material according to claim 1, characterized in that: In step (1), the carbon fiber has a diameter of 10-20 μm and a length of 0.5-3 mm.
3. The conductive rubber foam material according to claim 1, characterized in that: In step (1), the usage ratio of carbon fiber and nitric acid solution is 10 g: 100-200 mL, and the concentration of nitric acid solution is 30-68 wt %.
4. The conductive rubber foam material according to claim 1, characterized in that: In step (1), the stirring treatment condition is 50-80° C. for 30-60 min; and the mixture is washed with deionized water.
5. The conductive rubber foam material according to claim 1, characterized in that: In step (2), the concentration of aniline in the reaction solution is 0.1-0.5 mol / L, the concentration of hydrochloric acid is 1 mol / L; the ratio of the pretreated carbon fiber to the reaction solution is 5-10 g:500 mL; the concentration of the ammonium persulfate solution is 0.1-0.5 mol / L; and the volume ratio of the reaction solution to the ammonium persulfate solution is 1:
1.
6. The conductive rubber foam material according to claim 1, characterized in that: In step (2), an ammonium persulfate solution is added dropwise at 0-5°C; the reaction time is 4-8 hours; and the mixture is washed alternately with deionized water and ethanol for 3-5 times.
7. The conductive rubber foam material according to claim 1, characterized in that: In step (3), the concentration of 4-hydroxycinnamic acid is 0.05-0.2 mol / L, the concentration of EDC·HCl and NHS is 0.05-0.2 mol / L; and the ratio of polyaniline modified carbon fiber to activation solution is 10 g: 200-500 mL.
8. The conductive rubber foam material according to claim 1, characterized in that: In step (3), triethylamine is added to adjust the pH to 6-8; the reaction is stirred at 20-30° C. for 12-24 h; and the mixture is washed with DMF, ethanol, and deionized water for 3-5 times in sequence.
9. A method for preparing the conductive rubber foam material according to any one of claims 1 to 8, characterized in that: The steps include: The natural rubber is put into an internal mixer, plasticized at 120-125° C. for 10-15 minutes, and stored at room temperature for 48 hours for standby use; the plasticized natural rubber, butyl rubber, butadiene rubber, modified carbon fiber, carbon black, zinc oxide, stearic acid, and zinc stearate are put into an internal mixer for mixing, the material is turned over for the first time at 100-105° C., the material is turned over for the second time at 110-115° C., and the mixing is continued for 7-12 minutes; the material is turned over for the third time at 120-125° C., 1,4-di-tert-butyl peroxyisopropylbenzene is added and mixed for 4-7 minutes, and azodicarbonamide is added and mixed for 7-10 minutes to obtain a mixture, and the conductive rubber foam material is obtained after foaming.
Citation Information
Patent Citations
Graphene natural rubber polymer controlled electrostatic mixed foam material and preparation method thereof
CN110684245A
Foamed electromagnetic shielding rubber, as well as preparation method and application thereof
CN107245195A